Pemenuhan HAK Pendidikan pada Narapidana di Lembaga Pemasyarakatan (LAPAS) II A Sidoarjo - Fika Ardiana; Syalwa Shabrina Khunaifi; Lilik Sri Utami; M. Asif Nur Fauzi (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2021)
Lembaga Pemasyarakatan are institutions that have the functions and duties to accommodate, care for, and foster correctional students. Students who are in a correctional facility have the right to get education, both formal and non-formal, even though they are in a children's correctional institution, judging from their age which is still less than or equal to 18 years, they need to get the right to education as in formal / elementary education institutions , middle school, and high school. The importance of fulfilling the educational rights of child prisoners must be optimized in collaboration with the relevant education office and also provide facilities and infrastructure that are in accordance with minimum standards. However, in reality, the fulfillment of children's education rights still cannot be optimized because Class IIA Prison is a temporary convict place before a court decision is made. Keyword: Correctional Institutions, Child Prisoners, and the Right to Education